Casarett & Doull's essentials of toxicology - Klaassen, Curtis D.; Watkins, John B. (John Barr) III; Casarett, Louis J. (McGraw-Hill Medical, 2010)
"We are delighted to present an updated full color, edition of Essentials of Toxicology, which distills the major principles and concepts of toxicology that were described in detail in the seventh edition of Casarett and Doull's Toxicology: The Basic Science of Poisons. We are grateful to the colleagues who contributed to the seventh edition of Casarett and Doull's Toxicology: The Basic Science of Poisons; their contributions to the parent text served as the foundation for the chapters in this edition of Essentials of Toxicology. Essentials of Toxicology concisely presents the broad science of toxicology. Important concepts from anatomy, physiology and biochemistry have been included to facilitate the understanding of the principles and mechanisms of toxicant action on specific organ systems. It is hoped that the book will be useful to students in undergraduate and graduate courses in toxicology, as well as students from other disciplines, who want to have a strong foundation in toxicologic concepts and principles"--Provided by publisher.